Current Compensations in Emulsion Type Pharmaceutical Formulation: An Overview: Current Compensations in Emulsion Type Pharmaceutical Formulation: An Overview - Mod, Chandrakant (International Journal of Pharmaceutical & Biological Archive, 2018)
In modern years, the quantity of medicine and drug treatments has larger extremely which are moderately often more strong. Pharmacy research reveals exclusive data which is growing day by day. Emulsion are important dosage formulation they are continuously used from ancient time. In this overview we discuss the development of emulsion technology also focused on properties of emulsion & formulation methods by different equipment used for this consideration. With different identification tests. Multiple emulsion, Microemulsion, Non-aqueous emulsion, Liposome emulsion, Emulsion polymerization, Nanoemulsion are new trends in emulsion technology.